A Structural Equation Modelling Approach for College Students Financial Literacy - Simarmata, Justin Eduardo; Chrisinta , Debora (Journal of Research in Mathematics Trends and Technology, 2022)
This research explores the dynamics of financial literacy among students in shaping future financial well-being. Using Structural Equation Modeling (SEM), it aims to uncover the relationship between financial literacy and students’ interest in learning about finance. The data is derived from responses to a questionnaire from 200 students. The research reveals a path coefficient of 0.97 between financial literacy and literacy interest, indicating a strong positive relationship. This implies that 97% of the variation in financial literacy can be explained by literacy interest. Overall, the SEM model demonstrates a significant fit, providing valuable insights for enhancing financial literacy among college students.